Investigating The Expression Changes of miR-93-3p, NFATc1 and NFATc3 Genes in Peripheral Blood Mononuclear Cells (PBMC) of Breast Cancer Patients - Mansoreh Dastgir; Garshasb Rigi; Samira Ghaedmohammadi; Sedigheh Tahmasebi (Fasa University of Medical Sciences, 2024)
Background & Objectives: Breast cancer is the most lethal malignancy in women. miRNAs function as epigenetic regulators and contribute to the pathogenesis of breast cancer. Nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1) and 3 (NFATc3), are targeted by microRNA-93 (miR-93). This study aims to evaluate the expression of these genes in peripheral blood mononuclear cells (PBMCs) of healthy women and women with breast cancer. Materials & Methods: In this cross-sectional study, blood samples were collected from 20 healthy women and 20 women with early-stage breast cancer. After isolating peripheral blood mononuclear cells (PBMCs), RNA extraction and cDNA synthesis were performed. The expression of the desired genes was then examined by Real-Time Polymerase Chain Reaction (RT-PCR). Statistical analysis was conducted. A p-value less than 0.05 was considered statistically significant, and Student's t-test was used to evaluate the relative changes in gene expression. Results: The results demonstrated that the expression of NFATc1 and NFATc3 genes in peripheral blood mononuclear cells (PBMCs) of breast cancer patients was significantly reduced compared to their expression in healthy individuals. Conversely, the expression of the miR-93-3p gene was significantly lower in healthy women than in breast cancer patients (p < 0.05). Conclusions: This study investigated the expression of miR-93-3p and its downstream targets, the NFATc1 and NFATc3 genes, for the first time in peripheral blood mononuclear cells. The expression levels were shown to be significantly different in patients with breast cancer compared to healthy women. Keywords: